Taxi drivers and COVID‐19 in Jamaica: Occupationally related income decline and health behaviour. (3rd September 2021) - James, Kenneth; Thompson, Camelia; Chin‐Bailey, Cameal; Donaldson Davis, Kayon; Walters, Dawn; Holder Nevins, Desmalee
Abstract: Income and employment are recognised as social determinants of health. Occupationally related exposures and working conditions impact health behaviours. Taxi drivers have been recognised as an occupationally COVID‐19 at‐risk group. COVID‐19 threatens their lives and livelihoods. This study describes self‐reported income changes attributed to the COVID‐19 pandemic among taxi drivers. Associations between percentage change in income and reported prevention practices were ascertained. In May 2020, a cross‐sectional study was done among 282 taxi drivers in the Kingston and St. Andrew Metropolitan Area in Jamaica. Multi‐stage sampling was used to select taxi driver from seven hubs. Data collection utilised a 28‐item questionnaire. Self‐reported income before and during the COVID‐19 pandemic was ascertained and correlations between relative changes in income and COVID‐19 prevention practices were assessed. The median pre‐COVID‐19 monthly income was USD 1, 428.57 (IQR = 1, 467.26), about USD 51/day. Median monthly income since the COVID‐19 outbreak was USD 500 (IQR = 472.37), about USD 18/day, representing a 65% reduction in income. There was a statistically significant association between the relative change in income and the practice of wearing mask while transporting passengers. Generally, as the relative change (decline) in income increased, reported compliance with mask wearing decreased (Spearman's rho = −0.15, p  = 0.02). Taxi drivers have experienced marked decline in income due to the COVID‐19 pandemic, with implications for health practices and the maintenance of desired health behaviours. Authorities should be cognisant of the economic impact and COVID‐related consequences in the taxi industry, as they seek to develop COVID‐19 occupationally related prevention and control programmes.